The Retention Of Newly Qualified Chartered Accountants In A Large Financial Services Company - Mgoduka, Babalwa (Department of Construction Economics and Management, 2020)
Considering the increasing shortage of newly qualified chartered accountants in South Africa, this study focused on investigating factors that influence newly qualified chartered accountants to either leave or stay with their employing organisation. This study was conducted at a financial services organisation situated in Cape Town, which like all other financial institutions, would like to decrease the exit of newly qualified accounting professionals and ensure that skilled employees remain within the organisation.